2016
DOI: 10.1093/ofid/ofw246
|View full text |Cite
|
Sign up to set email alerts
|

Colonization With Vancomycin-Resistant Enterococci and Risk for Bloodstream Infection Among Patients With Malignancy: A Systematic Review and Meta-Analysis

Abstract: Background.Vancomycin-resistant enterococci (VRE) cause severe infections among patients with malignancy, and these infections are usually preceded by gastrointestinal colonization.Methods.We searched the PubMed and EMBASE databases (up to May 26, 2016) to identify studies that reported data on VRE gastrointestinal colonization among patients with solid or hematologic malignancy.Results.Thirty-four studies, reporting data on 8391 patients with malignancy, were included in our analysis. The pooled prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 41 publications
(115 reference statements)
6
49
5
3
Order By: Relevance
“…On the other hand, our finding was lower than studies reported from North America (21%), Asia (24%) and Europe (20%) [52]. Another study from Iran reported high rate of VRE (48.9%) among hospitalized patients [53].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, our finding was lower than studies reported from North America (21%), Asia (24%) and Europe (20%) [52]. Another study from Iran reported high rate of VRE (48.9%) among hospitalized patients [53].…”
Section: Discussioncontrasting
confidence: 86%
“…Stool, urine and blood were the most common specimens from which VRE were isolated. This is not surprising because enterococci have been reported as the most common organisms isolated from intestinal tract, urinary tract and blood stream infections [5,8,15,20,48,52,57,62].…”
Section: Discussionmentioning
confidence: 98%
“…The clinical significance of most MDR has not been fully determined, but they are usually assumed to be more threatening than their susceptible counterparts. For example, colonisation [5] and infection [6] with vancomycin-resistant enterococci may have a negative impact on outcome in cancer patients. In contrast, bacteraemia caused by methicillin-resistant Staphylococcus aureus may not be more dangerous than bacteraemia caused by susceptible strains [7,] whereas there is strong evidence that carbapenemase-producing Klebsiella spp.…”
Section: Bacterial Infections - Antibiotic Stewardshipmentioning
confidence: 99%
“…with VRE leads to an intestinal domination with Enterococci 31,32 and 100% 1,35,36. Based on this, it seems likely that previously VRE colonized might also have no increased risk for VRE infections.…”
mentioning
confidence: 91%
“…(VRE) is a frequent burden in patients with hematological malignancies worldwide. 1 Enterococci, mainly Enterococcus faecalis and Enterococcus faecium, are common commensals of the human intestine. However, they can cause severe infections such as urinary tract infections, blood stream infections, hepatobiliary sepsis, and endocarditis.…”
Section: Introductionmentioning
confidence: 99%